The Woman Next Door - Byrski, Liz (2016)
This novel deals with ageing and the different ways in which a group of neighbours, who have become friends, deal with it's challenges. The narrative embraces the changing nature of friendship and marriage over time, the timeless pull of romance and the need to accommodate or let go of the importance of connections to a working life. It continues my creative research and production on the subject of ageing women, introducing issues of mental health, the role of carers and the significance of community involvement in old age.